Bursty Bulk Flow Turbulence as a Source of Energetic Particles to the Outer Radiation Belt. Issue 11 (6th June 2022) - Ergun, R. E.; Usanova, M. E.; Turner, D. L.; Stawarz, J. E.
Abstract: We report observations of a Bursty Bulk Flow (BBF) penetrating close to the outer edge of the radiation belt. The turbulent BBF braking region is characterized by ion velocity fluctuations, magnetic field ( B ) variations, and intense electric fields ( E ). In this event, energetic (>100 keV) electron and ion fluxes are appreciably enhanced. Importantly, fluctuations in energetic electrons and ions suggest local energization. Using correlation distances and other observed characteristics of turbulent E, test‐particle simulations support local energization by E that favors higher‐energy electrons and leads to an enhanced energetic shoulder and tail in the electron distributions. The energetic shoulder and tail could be amplified to MeV energies by adiabatic transport into the radiation belt where | B | is higher. This analysis suggests that turbulence generated by BBFs can, in part, supply energetic particles to the outer radiation belt and that turbulence can be a significant contributor to particle acceleration. Plain Language Summary: Bursty Bulk Flows are thought to be the earthward‐traveling exhaust from magnetic reconnection events in the Earth's magnetotail. These plasma flows slow and divert as they approach Earth and, in doing so, can generate strong plasma turbulence. The electric field turbulence, in turn, appears to energize electrons and ions. The primary finding of this research is that the electron energization favors electrons that already have high energy, and therefore results in "acceleration" in which a relatively few particles receive a disproportionate share of the energy. Furthermore, turbulent regions of bursty bulk flows are shown to penetrate to the edge of the outer radiation belt. As such, bursty bulk flows are potentially a significant source or seed population for radiation belt electrons. Key Points: A bursty bulk flow near the outer radiation belt displays turbulent electric fields and enhanced fluxes of energetic ions and electrons Electrons appear to be locally accelerated by turbulent electric fields forming an energetic shoulder in the distribution Turbulent electric fields in the Bursty Bulk Flow braking region favors energization of the highest energy electrons